Evaluación de parámetros hematológicos del Búfalo de agua (bubalus bubalis) de la Hacienda Agrimroc de la Región Interandina. - Vivanco Calva, Mariela Esperanza (2020)
In this research study, entitled, "EVALUATION OF HEMATOLOGICAL PARAMETERS OF THE WATER BUFFALO (Bubalus bubalis) FROM THE AGRIMROC INTERANDINA REGION", to determine the hematological parameters of buffalo cattle, was its observing the cellular behavior of the biometric values and Biochemists, likewise carrying out a comparative analysis with other existing research in America that reflect truthful data, the research was carried out in the province of Azuay, working with 28 buffalo classified according to their age and sex in which it could be determined in general the average of Hematocrit 32.09 ± 0.83 (%), Hemoglobin 10.68 ± 0.26 (g / dL), Average hemoglobin concentration 33.6 ± 0.33 (g / dL), Leukocytes 10.98 ± 0.79 (K / µL), Granulocytes 3.86 ± 0.3 (8K / µL), Lymphocytes / Monocytes 65.46 (x10 ^ 9 / L), Platelets 191.54 ± 30.32 ( K / µL). The biochemical analysis obtained the following results, the general mean of Glucose 70.29 ± 3.33 (mg / dL), Creatinine 1.83 ± 0.08 (mg / dL), Ureic Nitrogen in Blood 10.32 ± 0 .6 (mg / dL), Total Protein 7.37 ± 0.26 (mg / dL), Albumin 2.95 ± 0.07 (mg / dL); Globulin 0.69 ± 0.03 (mg / dL), Alanine Aminotransferase 96.36 ± 6.5 (U / L), Alkaline phosphatase 149.32 ± 20.09 (U / L). The T of a variable was used for general parameters of biometry and biochemistry in the evaluation by sex; An ADEVA with a random design was used for the age variable.